The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/sym11030303
|View full text |Cite
|
Sign up to set email alerts
|

Train Regulation Combined with Passenger Control Model Based on Approximate Dynamic Programming

Abstract: Rescheduling is often needed when trains stay in segments or stations longer than specified in the timetable due to disturbances. Under crowded situations, it is more challenging to return to normal with heavy passenger flow. Considering making a trade-off between passenger loss and operating costs, we present a train regulation combined with a passenger control model by analyzing the interactive relationship between passenger behaviors and train operation. In this paper, we convert the problem into a Markov d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Hao et al [39] present a rescheduling approach based on a Markov decision process. It examines the interactive link between train operation and passenger behavior and reschedules trains considering dynamic passenger flow.…”
Section: Urban Rail Transit Reschedulingmentioning
confidence: 99%
“…Hao et al [39] present a rescheduling approach based on a Markov decision process. It examines the interactive link between train operation and passenger behavior and reschedules trains considering dynamic passenger flow.…”
Section: Urban Rail Transit Reschedulingmentioning
confidence: 99%
“…Focusing on the challenge of large passenger fow in interchange stations during peak periods, Li et al [32] constructed a collaborative optimization model of passenger fow control and train rescheduling with the goal of minimizing the weighted waiting time of passengers outside and inside stations. For large passenger fow scenarios, Hao et al [33] proposed a management strategy that can regulate the train operation time and control the number of passengers boarding a train with the help of the Markov decision process. Focusing on train delays of the high-demand and high-frequency line, Li et al [34] suggested a model predictive control-based method by taking the minimum of total delay as objective and the passenger control as constraints.…”
Section: Introductionmentioning
confidence: 99%
“…As pioneer studies of metro train regulation, Campion et al [2] and Van Breusegem et al [3] addressed the state feedback control of metro lines without considering operational constrains. Due to the large-scale, nonlinear, constrained, and stochastic features of metro transportation systems [4][5][6], model predictive control (MPC) [7][8][9] has become a widely used method in solving the train regulation problem. Grube and Cipriano [10] compared MPC strategy with the heuristic rule-based strategy for metro train regulation, showing that MPC strategy has better performance.…”
Section: Introductionmentioning
confidence: 99%